2021
DOI: 10.3389/fneur.2021.639822
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on (A)symmetry of Arcuate Fasciculus. A Short Review About Anatomy, Tractography and TMS for Arcuate Fasciculus Reconstruction in Planning Surgery for Gliomas in Language Areas

Abstract: Gliomas are brain tumors that are treated with surgical resection. Prognosis is influenced by the extent of resection and postoperative neurological status. As consequence, given the extreme interindividual and interhemispheric variability of subcortical white matter (WM) surgical planning requires to be patient's tailored. According to the “connectionist model,” there is a huge variability among both cortical areas and subcortical WM in all human beings, and it is known that brain is able to reorganize itself… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 76 publications
(28 reference statements)
0
12
0
Order By: Relevance
“…For some patients with slow-growing tumors such as gliomas involving language areas, the dominant hemisphere was found to be likely located right originally (15,30) or shift from left to right (31,32). Jehna and colleagues also reported that patients with gliomas in the left hemisphere and intact language function tended to have an AF that was symmetric or lateralized to the right (33), indicating that contralateral AF may involve in patients harboring a glioma in the dominant hemisphere and may facilitate the recovery from aphasia and the reorganization of the language brain network even after surgical damage (9). A tumor actually contralateral to the dominant hemisphere would definitely make a neurosurgeon less constrained during a total or extended resection.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…For some patients with slow-growing tumors such as gliomas involving language areas, the dominant hemisphere was found to be likely located right originally (15,30) or shift from left to right (31,32). Jehna and colleagues also reported that patients with gliomas in the left hemisphere and intact language function tended to have an AF that was symmetric or lateralized to the right (33), indicating that contralateral AF may involve in patients harboring a glioma in the dominant hemisphere and may facilitate the recovery from aphasia and the reorganization of the language brain network even after surgical damage (9). A tumor actually contralateral to the dominant hemisphere would definitely make a neurosurgeon less constrained during a total or extended resection.…”
Section: Discussionmentioning
confidence: 97%
“…DTT makes visualization of the AF possible, and the feasibility and accuracy have been confirmed (4)(5)(6)(7)(8). A few studies have so far focused on presurgical planning, DTT for AF, and postoperative outcome (9). Moreover, the correlation between asymmetry of reconstructed AF and language lateralization has been further investigated (10)(11)(12).…”
Section: Introductionmentioning
confidence: 92%
“…For example, a CST interruption can bring irreversible hemiplegia while cortical damage of the motor strip may result “only” in a focal motor deficit. As it concerns language, a similar consideration can be done: in fact, the classical localist view of “well-defined” Broca’s and Wernicke’s areas has shifted to a hodotopical view ( 41 , 43 , 44 ). In this novel understanding of language organization, there are two major subcortical complex networks constituted by the dorsal stream which is responsible for phonological tasks and a ventral stream in charge of semantic functions ( 43 , 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this novel understanding of language organization, there are two major subcortical complex networks constituted by the dorsal stream which is responsible for phonological tasks and a ventral stream in charge of semantic functions ( 43 , 45 ). Such language organization emphasizes the role of subcortical connections rather than the importance of definite cortical areas ( 44 , 46 48 ). Moreover, it has been shown that cortical areas can undergo brain plasticity phenomena, much more relevant than white matter tracts ( 6 , 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…This is especially important for tumors involving eloquent circuits, for example, the cortical/subcortical networks that control the cognitive and motor functions underlying communicative abilities, which are considered indispensable for daily life. In the past, the localizationist model assumed that cortical areas were specialized for neurological and cognitive functions [ 3 ]. Recent brain mapping methods have since been used to propose the connectionist model.…”
Section: Introductionmentioning
confidence: 99%